COMMUNITY PARTICIPATION IN DEVELOPMENT PLANNING IN TEGAL SARI MANDALA III DISTRICT MEDAN DENAI KOTA DISTRICT - Oktavia, Nini; Rangkuti, Bachtiar Ahmad Fani (MAP Observer: Jurnal Penelitian Administrasi Publik, 2024)
This study aims to examine community development planning in terms of facilities and infrastructure or Physical conditions and barriers to community participation in Participatory development planning. The research was conducted in the village of Tegal Sari Mandala III, Medan denai district, Medan city is an area that is known to be strategic with a fairly good community life. research form qualitative descriptive. Data collection techniques used in this study were conducted through interviews with related parties such as village officials, LPM, and the Participatory Development Planning Executive Committee for participatory development planning activities. In addition, other techniques used are observation and recording. The data analysis technique used is descriptive analysis. The findings show that the level of community involvement is positive. Due to the active participation and passive participation carried out by some of the people in the Tegal Sari Mandala III Village when the participation took place.